Effect of Perceived Social Support on Self-care Agency and Loneliness Among Elderly Muslim People - Dural, Gul; Budak, Funda Kavak; Ozdemir, Aysel A.; Gultekin, Abdurrezzak (Springer, 2022)
This study was conducted to investigate the effect of perceived social support on self-care agency and loneliness among elderly Muslim people. This study used a cross-sectional design and included 965 elderly individuals who met the inclusion criteria. There was a positive correlation between perceived social support and self-care agency and a negative correlation between perceived social support and loneliness in elderly muslim individuals (p < 0.05). It is recommended that psychiatric nurses should activate the social support mechanisms of elderly individuals, and necessary follow-ups to increase self-care agencies must be conducted.
Keywords: Perceived social support; Self-care agency; Loneliness; Elderly muslim people